2012
DOI: 10.1177/1753193412447494
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results after resection arthroplasty in Kienböck’s disease

Abstract: lunate and subsequent replacement with a tendon-ball implant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 3 publications
2
8
0
1
Order By: Relevance
“…In late-stage Kienböck's disease, the excision of lunate and replacement with silicone or tendon ball was described previously in the literature as a treatment option. [16][17][18][19][20][21][22][23][24][25] Silicone replacement caused foreign body reaction with severe reactive synovitis and carpal instability which led to unsatisfactory results. 20,28,29 In some series using tendon ball arthroplasty for treatment of Kienböck's disease, the authors reported that they used an additional tendon and free vascularized bone graft to substitute the cavity of the excised lunate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In late-stage Kienböck's disease, the excision of lunate and replacement with silicone or tendon ball was described previously in the literature as a treatment option. [16][17][18][19][20][21][22][23][24][25] Silicone replacement caused foreign body reaction with severe reactive synovitis and carpal instability which led to unsatisfactory results. 20,28,29 In some series using tendon ball arthroplasty for treatment of Kienböck's disease, the authors reported that they used an additional tendon and free vascularized bone graft to substitute the cavity of the excised lunate.…”
Section: Discussionmentioning
confidence: 99%
“…2,19 Tendon ball interposition arthroplasty for treatment of late-stage (stages III and IV) Kienböck's disease has been reported in literature with good results. 16,17,[20][21][22][23][24][25] In all of these articles, palmaris longus or pronator quadratus tendon was used. [20][21][22][23][24][25] In 2013, Karalezli et al reported a biomechanical cadaveric study using extensor carpi radialis longus (ECRL) tendon for interposition arthroplasty for treatment of Kienböck's disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, long-term surveys demonstrated, however, a marked tendency to develop severe synovitis and cyst formation caused by silicone particles destroying the joint (Kaarela et al, 1998; Kato et al, 1986; Schuind et al, 2008; Viljakka et al, 1987; Viljakka et al, 1995), and SLA was abandoned several years ago. Today, other methods of operative treatment have been adopted (Allan et al, 2001; Backaert et al, 1985; Mariconda et al, 2013; Ueba et al, 1999; Werber et al, 2013; Yajima et al, 2004; Zeplin and Ziegler, 2013). We found 20 years ago that in certain circumstances, silicone cyst formation had not developed even 20 years after SLA (Viljakka et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…따라서 수근골의 높이(Carpal height)를 유지하기 위해 일시적인 주상 유두골 고정술, 삼중 주상골 고정술, 혹은 외고정기를 이용하기도 한다 [9][10][11] . 건 충진술은 장수장건 내에 골핵(bone core)을 삽입하는 방 법, 장수장건만으로 부족 시 족저건을 첨가하는 방법 등을 비 롯해 여러 방법이 제시 되어 왔으며 [11][12][13][14][15][16]…”
unclassified